Food Security and Nutritional Status of Toddlers Post-Disaster in Palu City - Hartini, Diah Ayu; Faisal, Elvyrah; Mangun, Mardiani; Bahja, Bahja; Dewi, Nikmah Utami; Aiman, Ummu (Poltekita : Jurnal Ilmu Kesehatan, 2024)
Palu City is the capital of Central Sulawesi Province which is prone to earthquakes because there is a fault in the earth's crust known as the Palu-Koro fault. There were 3 disasters at once in Central Sulawesi, namely the earthquake, tsunami and liquefaction in 2018. Natural disasters can have an impact on various kinds of losses experienced by the community, including nutritional disorders and disrupted components of food security. Toddlers are the group most vulnerable to nutritional problems and food insecurity in disaster situations up to post-disaster. This study aims to determine household food security and nutritional status of children under five after the disaster in Palu City. This research is a descriptive type of research using a cross-sectional by looking at the relationship between household food security and the nutritional status of children under five after the disaster in Palu City. The sampling technique used purposive sampling with a total sample of 101 respondents consisting of mothers and toddlers. The instruments used were the USDA questionnaire to assess food security and measurements of length or height and weight to measure the nutritional status of children under five. Data collection used a USDA questionnaire to assess household food security and the BB/U index was used to assess the nutritional status of children under five. There is no significant relationship between food security and nutritional status of children under five after the disaster in Palu City. This can happen because children under five with nutritional status of normal or abnormal weight 76.24% come from families with high food security scores. In addition, the existence of good food distribution in Palu City after the disaster occurred was also a cause of good food availability.